Understanding the challenges of industrial carbon capture and storage: an example in a U.S. petrochemical corridor. Issue 1 (2nd January 2019) - Dismukes, David E.; Layne, Michael; Snyder, Brian F.
ABSTRACT: Industrial carbon capture and storage (CCS) is carbon capture from non-power, stationary emissions sources, typically involving high-purity emissions from a non-combustion exhaust stream. Industrial CCS activities represent a significant opportunity for reducing carbon emissions in concentrated geographic locations and a potential 'bridge' to more widespread CCS. This paper provides a summary of the opportunities for industrial CCS and market-based revenue streams, like those associated with enhanced crude oil recovery (EOR). The use of EOR changes the nature of carbon from being a pollutant to a valuable commercial input, which requires a judicious understanding of the technical industrial sequestration process, historic oil and gas operations, and the specific location and types of industrial carbon sources that can facilitate this type of carbon emissions mitigation strategy. We review literature on costs and summarise geospatial data to provide an overview of the potential for an integrated industrial CCS-EOR system in a petrochemical corridor.